Vytápění bytového domu - Jára, Marek (Vysoké učení technické v Brně. Fakulta stavební, 2020)
Téma této diplomové práce je návrh vytápění bytového domu. Teoretická část diplomové práce pojednává o spalinových cestách. Výpočtová část diplomové práce obsahuje návrh vytápění pomocí otopných deskových těles, podlahových konvektorů a systému podlahového vytápění. Zdroj tepla bude zhotoven pomocí kaskádově zapojených plynových kondenzačních kotlů. Součást výpočtů je příprava teplé vody, návrh zásobníku teplé vody a dalších potřebných zařízení soustavy. Část Projekt obsahuje technickou zprávu a modelaci chování podlahového vytápění za různých okrajových podmínek.

The theme of this diploma thesis is to design heating of the flat house. The theoretical part of this diploma thesis is about exhaust gases paths. The calculation part of this diploma thesis contains the design of the heating system by panel heaters, floor convectors and underfloor heating system. The heat source is the system of cascade-connected gas condensing boilers. The rest of this part are the calculations of the preparation of hot water, design of hot water storage tank and another necessary equipment of the system. The part Project is about technical report and simulation of behaviour of underfloor heating system in various marginal conditions.
Heating of flat house
Keywords: Spalinová cesta; komín; vytápění; systém; podlahové vytápění; otopná desková tělesa; konvektor; zdroj tepla; plynový kondenzační kotel; příprava teplé vody; zabezpečovací prvky; bytový dům; simulace.; Exhaust gases paths; chimney; heating; system; underfloor heating; panel heaters; convector; heat source; gas condensing boiler; preparation of hot water; safety equipment; flat house; simulation.